Cronobacter sakazakii: Emerging Public Health Threat for Infants (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Cronobacter sakazakii is a new pathogenic bacteria that is the leading cause of severe diseases that affect public health, mainly infants and neonates and immunocompromised persons. This bacterium is an isolated cause of severe infections such as necrotizing enterocolitis, meningitis, and bacteremia, with case fatalities ranging from 40 to 80%. The following cases are most vulnerable: Children under 3 because their immune system is poorly developed. Despite the relatively low case rates globally of C. sakazakii infections, evidence suggests that foodborne transmission, specifically through infant formula consumption, is a significant route of infection. The bacterium likes to be in dry places, which is why it is seen increasing in infant formula and powdered foods. Thus, the risk of getting infected is very high among the young. It is only in the recent past that researchers have been able to propose probable virulence factors in C. sakazakii, including outer membrane proteins and enzymes. Among these modes are the facilities that allow the bacterium to penetrate the gastrointestinal tract and the blood-brain barrier, which qualify the bacterium as lethal to the infant populations. Reducing contamination risks requires committed control measures that include better ways of manufacturing, sterilizing equipment, and educating caregivers. Disease surveillance and laboratory reporting on C. sakazakii cases should be stepped up to detect cases and control the disease. In conclusion, the primary strategies for minimizing the effects of C. sakazakii can be achieved through concerted efforts by the government, health departments, and the food processing sector to defend vulnerable groups.